Persistent Feeding and Swallowing Deficits in a Mouse Model of 22q11.2 Deletion Syndrome - Welby, Lauren; Caudill, Hailey; Yitsege, Gelila; Hamad, Ali; Bunyak, Filiz; Zohn, Irene E.; Maynard, Thomas; LaMantia, Anthony-Samuel; Mendelowitz, David; Lever, Teresa E. (Frontiers in Neurology, 2020)
Disrupted development of oropharyngeal structures as well as cranial nerve and brainstem circuits may lead to feeding and swallowing difficulties in children with 22q11.2 deletion syndrome (22q11DS). We previously demonstrated aspiration-based dysphagia during early postnatal life in the LgDel mouse model of 22q11DS along with disrupted oropharyngeal morphogenesis and divergent differentiation and function of cranial motor and sensory nerves. We now ask whether feeding and swallowing deficits persist in adult LgDel mice using methods analogous to those used in human patients to evaluate feeding and swallowing dysfunction. Compared to wild-type mice, videofluoroscopic swallow study revealed that LgDel mice have altered feeding and swallowing behaviors, including slower lick rates, longer inter-lick intervals, and longer pharyngeal transit times with liquid consistency. Transoral endoscopic assessment identified minor structural anomalies of the palate and larynx in one-third of the LgDel mice examined. Video surveillance of feeding-related behaviors showed that LgDel mice eat and drink more frequently. Furthermore, LgDel animals engage in another oromotor behavior, grooming, more frequently, implying that divergent craniofacial and cranial nerve structure and function result in altered oromotor coordination. Finally, LgDel mice have significantly increased lung inflammation, a potential sign of aspiration-based dysphagia, consistent with results from our previous studies of early postnatal animals showing aspiration-related lung inflammation. Thus, oromotor dysfunction, feeding, and swallowing difficulties and their consequences persist in the LgDel 22q11DS mouse model. Apparently, postnatal growth and/or neural plasticity does not fully resolve deficits due to anomalous hindbrain, craniofacial, and cranial nerve development that prefigure perinatal dysphagia in 22q11DS. This new recognition of persistent challenges with feeding and swallowing may provide opportunities for improved therapeutic intervention for adolescents and adults with 22q11DS, as well as others with a history of perinatal feeding and swallowing disorders.